Role of infection with Hymenolepis nana in alteration of some Biochemical, Immnunological and Histological parameters in Mice/Balb-C - Maroof Sabti Juma Al-Ammash (Acta Scientiarum. Animal Sciences, 2025)
The current study was conducted from November 2023 to February 2024 on 20 male laboratory mice. The current study evaluated the effect of infection with the dwarf worm on some biochemical and immunological parameters and some histological changes of the liver and intestine of laboratory mice. During the current study, liver enzymes, some cellular motility and immunoglobulin E were measured using ELISA technology by providing a set of work from well-known international companies. Histological sections of the liver and intestine of mice were also prepared for both the control and dwarf worm-infected groups. The current study showed significant differences between the levels of enzymes, cellular motility and immunoglobulin E levels by comparing the results of the infected group with the control group. In addition, the current study also showed changes in the liver and intestine tissues by comparing with the control group as well. It appears from the results of the current study that infection with the dwarf worm causes changes in liver functions and stimulates the immune response in addition to histological changes in both the liver and intestine.